Estimation of stature from facial measurements in northwest Indians - Sahni, Daisy; Sanjeev; Sharma, Parul; Harjeet; Kaur, Gagandeep; Aggarwal, Anjali (Legal medicine, 2010)
Estimation of stature is one of the important component in identification of human remains in forensic anthropology. The present investigation attempts to estimate stature from seven facial measurements of 300 (173 males and 127 females) healthy subjects between the ages of 18–70 years from Northwest India. Height of all the subjects was measured and facial measurements were taken. Data was subjected to statistical analysis like mean, standard deviation, multiplication factors, Karl Pearson’s correlation coefficient ( r), linear and multiple regression analyses using statistical package for social sciences (SPSS). The average height of the subjects was in the range of 154.3–178.3 cm in males and 155.1–168.4 cm in females. Estimated stature calculated by regression analysis of seven facial measurements was almost similar to mean actual stature in both males and females and the difference by using multiplication factors was found to be greater. Standard error of estimation (SEE) computed both by linear and multiple regression analyses was found to be low for the two sexes. Thus we can conclude that regression equations generated from facial measurements can be a supplementary approach for the estimation of stature when extremities are not available.